Daily field checking list by Walter Rosene, May 2, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, May 2, 1936. Plustek--flatbed